StoutQuest: the journal of research at University of Wisconsin-Stout, no.6, 2012-2013 - Poling, Jerry, 1958-; Flom, Hannah; Mell, Doug (University of Wisconsin--Stout. Provost’s Office, 2013)
StoutQuest is the UW-Stout annual journal of faculty and staff research. The journal highlights the growing and diverse scholarship and applied research that happens every day among faculty, staff and students of Wisconsin's Polytechnic University.
Pigeon Lake provides applied research experiences -- Faculty leads study to gain insight on retail management in China -- Federal grant funds faculty research projects -- Grant-funded program results in cool math research -- Research project connects softball, physics -- Art, construction, literature collaborative creates museum exhibit -- Professor's Hollywood connection helps student -- Professor guides student-run health clinic at food pantry -- Discovery Center researcher wins state award for fuel cell work -- Research intersects with Quantity Food Production -- Graphic communications management projects win national printing quality awards -- Social science class teaches research skills to Birchwood students -- Education class digs into research for teachers -- McNair scholar continues research in grad school -- Apparel design project receives national attention -- Associate professor's project blends history with technology -- Applied Research Center study contributes to student retention -- Four faculty earn national, state recognition -- Foundation supports research with special grants -- 2012 scholarly activity.
Keywords: Research--Periodicals; University of Wisconsin--Stout. Research Services; University of Wisconsin--Stout.